Analysis of Students' Motivation and Achievement: Comparing BAHASA INGGRIS Textbook and Nias Local Wisdom Materials: Analisis Motivasi dan Prestasi Siswa: Membandingkan Buku Ajar BAHASA INGGRIS dan Materi Kearifan Lokal Nias - Innes Lestari Zebua; Elwin Piarawan Zebua; Adieli Laoli; Riswan Zega (ITScience (Information Technology and Science), 2024)
English reading skills are essential for academic success, fostering comprehension, critical thinking, and motivation. Engaging reading materials, particularly those reflecting cultural relevance, like Nias local wisdom, enhance intrinsic motivation and learning achievement. This research uses a mixed-methods approach to assess textbook content with Nias-based texts to assess their motivational impact. Using a Sequential Explanatory Design, the study combines quantitative and qualitative methods for comprehensive insights. Quantitative tests measure reading comprehension and motivation, while qualitative interviews explore students' perceptions. Data integration ensures robust findings, guiding effective educational practices at SMA Negeri 1 Gunungsitoli. The research analyzed texts from the BAHASA INGGRIS textbook (